2018
DOI: 10.3389/fmicb.2018.02777
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study: Changes of Gut Microbiota in Post-surgery Colorectal Cancer Patients

Abstract: Colorectal cancer (CRC) is a growing health problem throughout the world. Strong evidences have supported that gut microbiota can influence tumorigenesis; however, little is known about what happens to gut microbiota following surgical resection. Here, we examined the changes of gut microbiota in CRC patients after the surgical resection. Using the PCoA analysis and dissimilarity tests, the microbial taxonomic compositions and diversities of gut microbiota in post-surgery CRC patients (A1) were significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 49 publications
4
35
0
Order By: Relevance
“…Our study indicated that, following curative resection, Fusobacterium was significantly decreased at both genus and phylum levels. Recently, one pilot study reported changes in gut microbiota 1 month after palliative surgery or radical surgery in patients with CRC [24] where, consistent with our results, alpha diversity decreased after surgery. In that study, pathogens such as Fusobacterium and Parvimonas decreased at the genus level following surgery, but Klebsiella, which often predicts gut flora dysbiosis, increased.…”
Section: Discussionsupporting
confidence: 91%
“…Our study indicated that, following curative resection, Fusobacterium was significantly decreased at both genus and phylum levels. Recently, one pilot study reported changes in gut microbiota 1 month after palliative surgery or radical surgery in patients with CRC [24] where, consistent with our results, alpha diversity decreased after surgery. In that study, pathogens such as Fusobacterium and Parvimonas decreased at the genus level following surgery, but Klebsiella, which often predicts gut flora dysbiosis, increased.…”
Section: Discussionsupporting
confidence: 91%
“…Data set collection and sequencing data preprocessing. The 16 data sets were labeled as Zeller (5), Flemer (32), Burns (33), Baxter (10), China_GBA (China Great Bay Area) (23), MAL2 (34), MAL1 (34), Zackular (9), Kostic (35), PNAS (36), Brazil (19), China_KM (China, Kunming) (37), China_SH (38), China_QD (China, Qingdao) (39), and China_SHTJ (40). Raw sequence data and metadata were retrieved from the NCBI or from the authors directly.…”
Section: Methodsmentioning
confidence: 99%
“…Cong et al [ 56 ] reported significantly reduced overall diversity in the fecal microbiota in post-surgery CRC patients compared to healthy individuals and pre-surgery CRC patients. This finding might reflect the further reduction in bacterial diversity as a result of perioperative antibiotic prophylaxis [ 31 ].…”
Section: Alterations Of Intestinal Microbiota Composition Followinmentioning
confidence: 99%